Facial Thermal Dynamics Analysis as an Indicator of Emotion and Physiological Stress: A Biophysical Study on College Students During Physics Learning - Aris Widodo; Uswatun Chasanah (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2025)
This research explores facial thermal dynamics as a non-invasive indicator of emotion and physiological stress in Indonesian students during physics learning, given the prevalence of mental health issues in this demographic. Academic stress triggers the body's stress response, causing measurable changes in skin surface temperature. Analyzing these variations offers a potential biomarker to assess physiological stress and its associated mental health risks. Using a quantitative approach, the study measured the facial temperature of four participants on their forehead, nose, and lips with a Uti120s thermal camera during four distinct stages of a physics lesson, with the thermographic data subsequently analyzed via Python to calculate temperature, radiation wavelength, heat transfer, and temporal temperature gradients. The average temperature increase was recorded on the forehead: Tmin = 33,86℃, Tmax = 35,34℃,Tincrement  = 1,48 ℃,  nose : Tmin = 30,56 ℃, Tmax = 34,27℃, Tincrement  = 3.32 ℃ and lip : Tmin = 29,82 ℃, Tmax = 34,07℃, Tincrement 3,88 ℃. This temperature increase was observed during the pre-lecture and core lecture stages, then decreased after the quiz. The emitted infrared wave radiation ranges from 9.42μm (forehead), 9.47μm (nose), and 9.48μm (lips), high radiation heat transfer in the forehead area and minimal in the lip area. The temperature gradient is positive at the beginning of the lecture and negative at the end which are not visible to the naked eye but can be captured by thermal cameras as biomarkers of physiological stress. Although there were temperature changes, the detected emotions were mostly neutral, indicating that the physics learning process triggers physiological stress but does not significantly affect mental health negatively in this initial observation.